Fluorescense laparoscopy in patients with gastric cancer - V. A. Lukin; E. V. Filonenko; L. A. Vashakmadze (Biomedical Photonics, 2013)
The results of fluorescence laparoscopy in 60 patients with gastric cancer in P.A.Herzen MCRI are represented in the article. All patients had gastric cancer stage III. Undifferentiated cancer was diagnosed in 3 (5%) patients, signet ring cell carcinoma – in 42 (70%), low differentiated adenocarcinoma – in 15 (25%). Fluorescence diagnosis was performed using fluorescence laparoscope by Carl Storz (Germany) with wavelengths 380-460 nm and alasens given per os at a dose of 30 mg/kg body weight 3 h before study. During the investigation the examination of parietal and visceral peritoneum, great omentum with instrumental revision of pelvic organs was made. The technique of fluorescence diagnosis and assessment of its results are described. According to results of the study occult tumor microdissemination over peritoneum was detected in 10 (16.7%) patients. The sensitivity of fluorescence laparoscopy in patients with gastric cancer accounted for 87.5%, specificity – 76%. The data of fluorescence diagnosis allowed to perform staging of tumor process and influenced on following management.